La concepción de la naturaleza orgánica y el funcionalismo de lo mental en Aristóteles (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The objective of this research is to demonstrate that the Aristotelian theory of the soul is compatible with a functionalist conception of the mental. For this purpose, the concept of nature will be analyzed –particularly of organic nature– in the philosophy of Aristotle. From this, the theory of the Aristotelian soul is shown to be compatible with functionalist principles, which also applies to the specific case of how the sensory-perceptive system operates for the Stagirite.